Congruence in Exchange: The Influence of Supervisors on Employee Performance in Family Firms. (March 2019) - McLarty, Benjamin D.; Vardaman, James M.; Barnett, Tim
A pluralistic focus on economic and noneconomic goals creates dissonance for family firm employees. Drawing on social exchange theory, this study explores the idea that congruence between supervisor familial status and importance placed on socioemotional wealth aids in resolving this dissonance and allows committed employees to translate their efforts into better performance. The three-way interaction results show that committed employees working for congruent supervisors experienced higher task and citizenship performance. Supervisor incongruence resulted in the opposite effect. These findings suggest supervisor genuineness is vital to employee performance because of the dissonance associated with the pluralistic goal orientation in family firms.